Dementia assessment and diagnostic practices of healthcare workers in rural southwestern Uganda: a cross-sectional qualitative study - Ronald Kamoga; Godfrey Z. Rukundo; Edith K. Wakida; Gladys Nakidde; Celestino Obua; Stephanie S. Buss (BMC, 2019)
Abstract Background An estimated 50 million people worldwide have Alzheimer's disease and related dementias (ADRD), and this number is projected to increase with the growth of the aging population, with the largest growth occurring in low and middle-income countries. Diagnostic coverage for dementia is estimated to be only 5-10% in low- and middle-income countries. Timely diagnosis of ADRD could prompt early access to information, medical treatments, and support for caregivers. The aim of this study was to assess how healthcare workers in rural southwestern Uganda assess for and diagnose ADRD. Methods We used in-depth interviews to investigate the medical knowledge and clinical practices surrounding ADRD diagnoses among 42 healthcare workers employed at mid-tier health facilities in southwestern Uganda. Qualitative content analysis was used to identify distinct categories and themes. Results Our findings show that healthcare workers without specific mental health training assessed and diagnosed dementia based on history and physical examination alone. On the other hand, healthcare workers with some specialized training in mental health were more likely to use neuropsychological tests, blood tests, urine tests, and brain imaging in the diagnosis of dementia. Collateral history from caregivers was noted to be very important in proper assessment and diagnosis of dementia among all categories of healthcare workers. The majority of healthcare workers regarded memory loss as part of the normal aging process and reported that it does not need any specific treatment. Other healthcare workers could recognize signs and symptoms of dementia, but focused on managing other medical problems at the expense of assessing cognitive decline and mental health. Diagnostic practices did not differ based on age, years of experience, or gender of the healthcare workers. Conclusion These results indicate that specialized training in mental health among healthcare workers is crucial for the assessment and diagnosis of ADRD in rural southwestern Uganda.